MicroRNA profiling in MDA-MB-231 human breast cancer cell exposed to the Phaleria macrocarpa (Boerl.) fruit ethyl acetate fraction (PMEAF) through IIlumina Hi-Seq technologies and various in silico bioinformatics tools - Kavitha, Nowroji; Vijayarathna, Soundararajan; Shanmugapriya, -; Oon, Chern Ein; Chen, Yeng; Kanwar, Jagat Rakesh; Punj, Vasu; Sasidharan, Sreenivasan (Elsevier, 2018)
Ethnopharmacological relevance Phaleria macrocarpa (Scheff) Boerl, is a famous traditional medicinal plant which exhibited cytotoxicity against various cancerous cells. Traditionally, P. macrocarpa has been used to control cancer, impotency, hemorrhoids, diabetes mellitus, allergies, liver and heart disease, kidney disorders, blood diseases, acne, stroke, migraine, and various skin diseases. Aim of the study Recent studies have demonstrated a potent anticancer potential of P. macrocarpa, especially against HeLa cell. The objective of this study was to investigate the regulation of miRNAs on MDA-MB-231 treated with P. macrocarpa ethyl acetate fraction (PMEAF). Materials and methods The regulation of miRNAs on MDA-MB-231 cells treated with PMEAF was studied through IIlumina, Hi-Seq. 2000 platform of Next Generation Sequencing (NGS) and various in silico bioinformatics tools. Results The PMEAF treatment against MDA-MB-231 cells identified 10 upregulated and 10 downregulated miRNAs. A set of 606 target genes of 10 upregulated miRNAs and 517 target genes of 10 downregulated miRNAs were predicted based on computational and validated databases by using miRGate DB Query. Meanwhile, results from DAVID Bioinformatics Resources 6.8 specified the functional annotation of the upregulated miRNAs involvement in cancer pathway by suppressing the oncogenes and downregulating miRNAs by expressing the tumour suppressor genes in the regulation of apoptosis pathway. Conclusion In conclusion, the results of this study proved that PMEAF is a promising anticancer agent with high cytotoxicity against MDA-MB-231 breast cancer cells and it induced apoptotic cell death mechanism through the regulation of miRNAs. PMEAF might be the best candidate for developing more potent anticancer drugs or chemo preventive supplements.